Relationship Between Breastfeeding and Obesity Among 7 Years Old Children in Libya - Hussein, Fathia (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. The current study aimed to investigate the relationship between infant-feeding variables and body mass index BMI in a group of Libyan children aged 7 years. Methods. A cross-sectional study was conducted to investigate the weight status and the relationship of infant-feeding variables with BMI, in a group of libyan children in Albayda,140 student of both sexes in elementary schools (aged 7 years) was selected from different educational districts of Albayda .The purposes of research was explained to mothers and written consent was obtained from them, weights and heights of children was measured, Data on breastfeeding (BF), formula-feeding, and the timing of introduction of complementary foods (CF), was collected from the mothers using a questionnaire. Results. The 2.8% of the children were underweight, and the prevalence of overweight 30 % respectively, Total time of BF and duration of exclusive BF were not associated with childhood BMI. The timing of introduction of CF was inversely related to childhood BMI after controlling for other variables (β:-0.34; 95% CI:-0.58,-0.10). Children with an early introduction of CF had significantly higher mean BMI (p for linear trend=0.012). Conclusion. Overweight and obesity are nutritional problems among 7 years old children in Libya. Preventive strategies are needed to prevent further increases in the prevalence of overweight and obesity.